3-d applied element method for pp-band retrofitted masonry - Worakanchana, K.; Mayorca, P.; Guragain, R.; Sathiparan, N.; Meguro, K. (My University, 2008)
In this study, we have proposed a new 3-D Applied Element Method (AEM) as an analysis tool for understanding the polypropylene band retrofitted masonry behavior which will be benefit in the future design process and increase the degree of freedoms of failure mode. Unlike the previous version of 3-D AEM, elements can be any rectangular prism which helps reducing the number of elements. Brick and mortar springs are represented by using different spring properties. Nonlinear constitutive law of the mortar spring employed the Gambarotta model which considers the material softening. Polypropylene band is modeled as beam element using plastic constitutive law connected together with the masonry by elastic spring representing the polypropylene band to brick connector. The numerical simulation of non-retrofitted and retrofitted out of plane wallets shows that with the suitable selected parameter the behavior of masonry can be closely reproduced
Keywords: Applied Element Method; Masonry